ANALYSIS OF VITAMIN C AND B1 LEVELS IN SENDUDUK FRUIT (Melastoma malabathricum L.) USING UV-VIS SPECTROPHOTOMETRY METHOD - Rejeki Geubrina Putri; Muhammad Nasir; Abdul Gani (Chimica Didactica Acta, 2020)
The fruit of "senduduk" contains a variety of nutrients and vitamins including vitamin C and B1. This study aims to determine the levels of vitamins C and B1 in young and ripe senduduk fruit that grows in coastal areas and in the mountains. The sample of the fruit was extracted with water. The absorbance of the extract of the fruit was then measured using UV-Vis spectrophotometry for vitamin C at a wavelength of 250 nm, while for vitamin B1 was measured at 420 nm. The results showed that vitamin C levels were (G1 = 0.34; G2 = 0.29%; P1 = 0.35; and P2 = 0.31)%, vitamin B1 was (G1 = 0.21; G2 = 0, 10%; P1 = 0.28; and P2 = 0.18)%. The results of the study can be concluded that there is a significant difference in vitamin C levels between young and old fruit, but it is not significantly different for the difference in the place of growth. There is a significant difference in vitamin B1 levels between young and ripe senseng fruit.